Adipocyte-Specific Glucocorticoid Inactivation Protects Against Diet-Induced Obesity - Kershaw, Erin E. (2005)
Local glucocorticoid (GC) action depends on intracellular GC metabolism by 11β-hydroxysteroid dehydrogenases (11βHSDs). 11βHSD1 activates GCs, while 11βHSD2 inactivates GCs. Adipocyte-specific amplification of GCs through transgenic overexpression of 11βHSD1 produces visceral obesity and the metabolic syndrome in mice. To determine whether adipocyte-specific inactivation of GCs protects against this phenotype, we created a transgenic model in which human 11βHSD2 is expressed under the control of the murine adipocyte fatty acid binding protein (aP2) promoter (aP2-h11βHSD2). Transgenic mice have increased 11βHSD2 expression and activity exclusively in adipose tissue, with the highest levels in subcutaneous adipose tissue, while systemic indexes of GC exposure are unchanged. Transgenic mice resist weight gain on high-fat diet due to reduced fat mass accumulation. This improved energy balance is associated with decreased food intake, increased energy expenditure, and improved glucose tolerance and insulin sensitivity. Adipose tissue gene expression in transgenic mice is characterized by decreased expression of leptin and resistin and increased expression of adiponectin, peroxisome proliferator–activated receptor γ, and uncoupling protein 2. These data suggest that reduction of active GCs exclusively in adipose tissue is an important determinant of a favorable metabolic phenotype with respect to energy homeostasis and the metabolic syndrome.